Pre-tibial myxedema: treatment with intralesional corticosteroid - Luana Oliveira Ramos; Paloma Corrêa Mattos; Giuseppe Lemos Pertoti de Figueredo; Alef Alioscha Andrade Maia; Sandra Adolfina Reys Romero (Sociedade Brasileira de Dermatologia, 2015)
Abstract The pretibial myxedema is a manifestation of Graves' disease characterized by accumulation of glycosaminoglycans in the reticular dermis. The dermopathy is self-limiting but in some cases may cause cosmetic and functional damage. Conventional treatment is use of topical steroids under occlusive dressing, however the intralesional application has shown good results. We present a case of pretibial myxedema treated with single injection of intralesional corticosteroid.